Reading the crisis: legal, philosophical and literary perspectives - Augusti, Eliana (Historia del Derecho, 2017)
Almost a decade has passed since the outbreak of the economic crisis; from its original nucleus, its effects have quickly affected the social and geopolitical fields. Such wide impact and its complex implications make the crisis an object susceptible of multiple readings. The particular aim of the studies collected in this volume is to explore the impact of the crisis on law, culture and society, in order to test the depth of the problem, by comparing the analytical perspectives obtainable from legal and human sciences. The book focuses on three main issues: the crisis as a social object, in order to consider the crisis in terms of its attributing force; the problem of democracy, which is becoming an increasingly central question now, as the changes imposed by the crisis have begun to settle down; the interdisciplinary challenge that, in time of crisis, questions paradigms of knowledge, competences and methods, in order to enable an heuristic dialogue between human, social and legal sciences.